TAT-HSP27 Peptide Improves Neurologic Deficits via Reducing Apoptosis After Experimental Subarachnoid Hemorrhage - Zhou, Xiao-yan; Sun, Jing-yi; Wang, Wei-qi; Li, Shu-xian; Li, Han-xia; Yang, Hui-juan; Yang, Ming-feng; Yuan, Hui; Zhang, Zong-yong; Sun, Bao-liang; Han, Jin-Xiang (Frontiers in Cellular Neuroscience, 2022)
Cell apoptosis plays an important role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). Heat shock protein 27 (HSP27), a member of the small heat shock protein family, is induced by various stress factors and exerts protective role on cells. However, the role of HSP27 in brain injury after SAH needs to be further clarified. Here we reported that HSP27 level of cerebrospinal fluid (CSF) is increased obviously at day 1 in patients with aneurysmal subarachnoid hemorrhage (aSAH), and related to the grade of Hunt and Hess (HH), World Federation of Neurological Surgeons (WFNS) and Fisher. In rat SAH model, HSP27 of CSF is increased at first and then obviously declined; overexpression of HSP27, not knockdown of HSP27, attenuates SAH-induced neurological deficit and cell apoptosis in basal cortex; overexpression of HSP27 effectively suppresses SAH-elevated the activation of Mitogen-Activated Protein Kinase Kinase 4 (MKK4), the c-Jun N-terminal kinase (JNK), c-Jun and caspase-3. In an in vitro hemolysate-damaged cortical neuron model, HSP2765-90 peptide effectively inhibits hemolysate-induced neuron death. Furthermore, TAT-HSP2765-90 peptide, a fusion peptide consisting of trans-activating regulatory protein (TAT) of HIV and HSP2765-90 peptide, effectively attenuates SAH-induced neurological deficit and cell apoptosis in basal cortex in rats. Altogether, our results suggest TAT-HSP27 peptide improves neurologic deficits via reducing apoptosis.